Trends in mortality from cancer of the uterus in Canada and in England and Wales. - Kinlen, L; Doll, R (1973)
The results show that the mortality from cervix cancer has declined materially in the last 10 yr, particularly under 45 yr of age, but that there is very little difference between the experience in British Columbia, Ontario and other parts of Canada. Only at ages 45-64 does British Columbia appear to have had any appreciable advantage. In England and Wales the mortality from cancer of the cervix at ages 20-44 years has been declining over the past decade though less rapidly than in Canada. In contrast to Canada, the mortality at ages 45-64 years has remained fairly constant.